Hydrogen-Releasing Micromaterial Dressings: Promoting Wound Healing by Modulating Extracellular Matrix Accumulation Through Wnt/β-Catenin and TGF-β/Smad Pathways - Pengxiang Zhao; Yufei Li; Boyuan Guo; Ziyi Liu; Xujuan Zhang; Mengyu Liu; Xuemei Ma (Pharmaceutics)
Background: Wound healing is a complex and intricate biological process that involves multiple systems within the body and initiates a series of highly coordinated responses to repair damage and restore integrity and functionality. We previously identified that breathing hydrogen can significantly inhibit early inflammation, activate autologous stem cells, and promote the accumulation of extracellular matrix (ECM). However, the broader functions and downstream targets of hydrogen-induced ECM accumulation and tissue remodeling are unknown in the wound-healing process. Methods: Consequently, this thesis developed a hydrogen sustained-release dressing based on a micro storage material and reveals the mechanism of hydrogen in treating wound healing. Upon encapsulating the hydrogen storage materials, magnesium (Mg), and ammonia borane (AB), we found that SiO2@Mg exhibits superior sustained-release performance, while SiO2@AB demonstrates a higher hydrogen storage capacity. We used a C57/BL6 mouse full-thickness skin defect wound model to analyze and compare different hydrogen dressings. Results: It was identified that hydrogen dressings can significantly improve the healing rate of wounds by promoting epithelialization, angiogenesis, and collagen accumulation in wound tissue, and that the effect of slow-release dressings is better than of non-slow-release dressings. We also found that hydrogen dressing can promote transcriptome-level expression related to cell proliferation and differentiation and ECM accumulation, mainly through the Wnt1/β-catenin pathway and TGF-β1/Smad2 pathway. Conclusions: Overall, these results provide a novel insight into the field of hydrogen treatment and wound healing.